Microsatellite primers for three Western Atlantic Farfantepenaeus prawn species - Maggioni, Rodrigo (2002)
Microsatellite loci were identified for three closely related penaeid species, Farfantepe-naeus subtilis, F. paulensis and F. sp., from genomic libraries enriched for CA repeats. Sevenout of nine highly polymorphic loci detected were amplified across all three species.Between four and 64 alleles were recorded per locus (average = 36). The average observedheterozygosity ranged from 0.094 to 0.897 (mean = 0.613), while the expected heterozygosityranged from 0.091 to 0.985 (mean = 0.822)